KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAME TOURNAMENT - Sandi Bela; Rohman Rohman; Ria Erviana (Program Studi PGSD Universitas Flores, 2024)
The main issue in mathematics education at SMP Negeri 5 Sungai Rotan is the students' low understanding of mathematical concepts, with a mastery level of less than 70%. To address this problem, this study aims to evaluate the effectiveness of the Teams Games Tournament (TGT) cooperative learning model in improving students' understanding of mathematical concepts. The research utilized a quasi-experimental method with a nonequivalent control group design, involving 60 seventh-grade students. The experimental class was taught using the TGT model, while the control class followed a conventional teaching approach. The research instruments included a mathematical understanding test, validated by experts and tested for reliability using the alpha coefficient. The results of the analysis showed that the students in the experimental group scored significantly higher than those in the control group, with a p-value of 0.001 < 0.05. Additionally, the TGT model proved effective not only in enhancing mathematical understanding but also in developing students' collaboration, communication, creativity, and critical thinking skills. This research contributes to the application of innovative learning models in mathematics, particularly in fostering more active and interactive learning environments.